Matrix metalloproteinase-9 is involved in chronic lymphocytic leukemia cell response to fludarabine and arsenic trioxide. - Irene Amigo-Jiménez (Public Library of Science (PLoS), 2014)
Background Matrix metalloproteinase-9 (MMP-9) contributes to chronic lymphocytic leukemia (CLL) pathology by regulating cell migration and preventing spontaneous apoptosis. It is not known if MMP-9 is involved in CLL cell response to chemotherapy and we address this in the present study, using arsenic trioxide (ATO) and fludarabine as examples of cytotoxic drugs. Methods We used primary cells from the peripheral blood of CLL patients and MEC-1 cells stably transfected with an empty vector or a vector containing MMP-9. The effect of ATO and fludarabine was determined by flow cytometry and by the MTT assay. Expression of mRNA was measured by RT-PCR and qPCR. Secreted and cell-bound MMP-9 was analyzed by gelatin zymography and flow cytometry, respectively. Protein expression was analyzed by Western blotting and immunoprecipitation. Statistical analyses were performed using the two-tailed Student's t-test. Results In response to ATO or fludarabine, CLL cells transcriptionally upregulated MMP-9, preceding the onset of apoptosis. Upregulated MMP-9 primarily localized to the membrane of early apoptotic cells and blocking apoptosis with Z-VAD prevented MMP-9 upregulation, thus linking MMP-9 to the apoptotic process. Culturing CLL cells on MMP-9 or stromal cells induced drug resistance, which was overcome by anti-MMP-9 antibodies. Accordingly, MMP-9-MEC-1 transfectants showed higher viability upon drug treatment than Mock-MEC-1 cells, and this effect was blocked by silencing MMP-9 with specific siRNAs. Following drug exposure, expression of anti-apoptotic proteins (Mcl-1, Bcl-xL, Bcl-2) and the Mcl-1/Bim, Mcl-1/Noxa, Bcl-2/Bax ratios were higher in MMP-9-cells than in Mock-cells. Similar results were obtained upon culturing primary CLL cells on MMP-9. Conclusions Our study describes for the first time that MMP-9 induces drug resistance by modulating proteins of the Bcl-2 family and upregulating the corresponding anti-apoptotic/pro-apoptotic ratios. This is a novel role for MMP-9 contributing to CLL progression. Targeting MMP-9 in combined therapies may thus improve CLL response to treatment.